Effective prover for minimal inconsistency logic - Neto, Adolfo Gustavo Serra Seca (2006)
In this paper we present an e ective prover for mbC, a minimal inconsistency logic. The mbC logic is a paraconsistent logic of the family of logics of formal inconsistency. Paraconsistent logics have several philosophical motivations as well as many applications in Arti cial Intelligence such as in belief revision, inconsistent knowledge reasoning, and logic programming. We have implemented the KEMS prover for mbC, a theorem prover based on the KE tableau method for mbC. We show here that the proof system on which this prover is based is sound, complete and analytic. To evaluate the KEMS prover for mbC, we devised four families of mbC-valid formulas and we present here the rst benchmark results using these families.